Development opportunities of biomass-based ethanol production in relation to starch- and cellulosebased bioethanol production - Balla, Zoltán (Acta Agraria Debreceniensis, 2013)
The biomass is such a row material that is available in large quantities and it can be utilizied by the biotechnology in the future. Nowadays the technology which can process ligno cellulose and break down into fermentable sugars is being researched. One possible field of use of biomass is the liquid fuel production such as ethanol production. Based on the literary life cycle analysis, I compared the starch-based (first generation) to cellulose-based (second generation) bioethanol production in my study considering into account various environmental factors (land use, raw material production, energy balance). After my examination I came to the conclusion that the use of bioethanol, independent of its production technology, is favorable from environmental point of view but the application of second generation bioethanol has greater environmentally benefits.